Efeito deletério da água em misturas asfálticas com adição de ligante modificado com polímero e de cal - Barboza Junior, Valdir dos Santos (2018)
Moisture damage is one of the major causes of premature failure of asphalt concrete. The evaluation of the deleterious effect of water in asphalt mixtures with the addition of polymer modified binder and lime by mechanical tests becomes important to analyse the moisture damage on the asphalt mixtures behaviour and to search for ways to decrease the action of water. The aim of this study is to evaluate, in the laboratory, the deleterious effect of water in asphalt mixtures with different types of aggregates, with and without addition of lime and using conventional and polymer modified asphalt binders. The properties stiffness, permanent deformation and cohesion/adhesion in asphalt mixtures were verified. Eight asphalt mixtures with identical aggregate strutures were used according to range C of DNIT 031/2006 - ES, measured by the Superpave methodology, which were submitted to the following tests: Resilience Module (RM) and Complex Moduli; tensile strength by diametrical compression (RT); Flow Number (FN); moisture induced damage and in addition to these the AASHTO T 283 protocol was used for the FN and Complex Modulus tests to evaluate the deleterious effect of water on these tests. In this case the mixtures were divided into two groups: group 1 without the conditioning cycle and group 2 with the conditioning cycle. This way was possible to obtain the dynamic moduli retained, the phase angle retained and the Flow Number retained (FNR). The Complex Modulus analysis results were conducted by the 2S2P1D modelling. For the MR test, it was possible to verify that adding lime into the asphalt mixtures increased by an average of 1.23 times the MR results. For most mixtures, the replacement of the CAP 50/70 binder for the AMP 60/85 decreased the MR values. In the complex modulus test the addition of lime and the type of binder were the factors that most affected the stiffness of the asphalt mixtures. It is observed that the samples consisted in CAP 50/70 showed higher values of loss modulus, therefore with a higher viscous behaviour and higher storage modulus values when compared to asphalt mixtures containing AMP 60/85. This fact also occurs with lime mixtures. The mixtures consisted of AMP 60/85 showed higher RT values than mixtures with CAP 50/70. This fact repeated in the comparison mixtures with and without lime. In the moisture induced damage (Modified Lottman) test all the blends obtained RRT values above 80%. In the FN test, the asphalt mixtures composed by modified binder and lime showed the highest values of FN. In the complex modulus test, after the conditioning cycles, they showed a higher viscous behaviour and higher storage modulus than the group 1 mixtures. Regarding the FNR, 50% of the mixtures suffered a decrease in FN values due to the action of water. Through the results was possible to notice that using the modified binder and inserting lime on asphalt mixtures provides tensile strength and permanent deformation increase.